Cassese's international criminal law - Cassese, Antonio, editor; Baig, L., (Laurel) editor; Fan, M., (Mary) editor; Whiting, A., (Alex) editor; Gaeta, Paola, editor; Gosnell, Christopher, editor (Oxford : Oxford University Press, 2013)
Provides a clear account of the main substantive and procedural aspects of international criminal law. Adopting a combination of the classic common law and more theoretical approaches to the subject, it discusses: the historical evolution of international criminal law; the legal definition of the so-called core crimes (war crimes, crimes against humanity, genocide) plus aggression, torture and terrorism; the forms and modes of criminal responsibility; and the main issues related to the prosecution and punishment of international crimes at the national and international level, including amnesties, statutes of limitations, and immunities.
Fundamentals of international criminal law -- The principal of legality -- The elements of international crimes, in particular, the mental element -- War crimes -- Crimes against humanity -- Genocide / revised by Paola Gaeta -- Torture and aggression / revised by Mary Fan -- Terrorism -- Perpetration : in particular joint and indirect perpetration / revised by Laurel Baig -- Omission liability and superior responsibility / revised by Laurel Baig -- Other modes of criminal liability and inchoate crimes / revised by Laurel Baig -- Justification and excuses / revised by Christopher Gosnell -- Obedience to superior orders and official capacity / revised by Christopher Gosnell and Paola Gaeta -- International criminal courts -- The repression of international crimes in domestic jurisdictions / revised by Paola Gaeta -- International versus national jurisdiction / revised by Alex Whiting -- Legal impediments to the exercise of criminal jurisdiction -- The adoption of the essential features of the adversarial system / revised by Christopher Gosnell -- Investigation and trial before international criminal courts / revised by Christopher Gosnell -- Appeals and enforcement / revised by Laurel Baig.
Revised edition of: International criminal law, second edition, 2008.
Includes bibliographical references and index.
Keywords: International crimes; Criminal procedure (International law); Criminal jurisdiction